PERANCANGAN GEDUNG SERBAGUNA FAKULTAS ILMU SOSIAL UNIVERSITAS NEGERI PADANG - Alland Aristo Ryu; Drs. Revian Body, MSA (CIVED, 2019)
Abstract— The background of this design is the lack of infrastructure in the Faculty of Social Sciences of Universitas Negeri Padang, including a multipurpose building as a place for student activities and can also be used for meeting or other activities. The stages of design are programming, planning and design. Primary data were obtained from location surveys and interview with owners, while secondary data were obtained from the results of literature study and local regulations. Macro analysis technique was used to analyze the location / site while micro analysis was used to analyze the design objects. The results of the design is a multipurpose building area of 1,586.39 m2, which include the main hall, podium area, 2 units dressing room, lobby, 2 units lavatory hall, warehouse and tribune on the 2nd floor. For educational facilities, spaces provided  are 6 units lecture room and 6 units student lavatory. The building budget plan is Rp 8,613,240,000.00. Keywords: Design, Multipurpose Building